A HIGH‐THROUGHPUT CLINICAL ASSAY FOR TESTING DRUG FACILITATION OF EXPOSURE THERAPY. Issue 7 (2nd January 2013) - Rodebaugh, Thomas L.; Levinson, Cheri A.; Lenze, Eric J.
Abstract : Objective: Several studies have demonstrated that D‐cycloserine (DCS) facilitates exposure therapy. We developed a standardized test of this facilitation (i.e., a clinical assay), with the goal of testing for facilitation more quickly and inexpensively than a full clinical trial. Method: We developed a standardized brief exposure in which participants with social anxiety disorder gave a videotaped speech. Participants were randomized to receive a single capsule of 250 mg DCS or a matching placebo prior to preparation for the speech. Distress levels were rated during the speech and again, approximately 1 week later, during a speech in an identical situation. Our primary measure of DCS's exposure‐facilitating effect was between‐session habituation: whether or not the participants showed less distress during the second speech compared to the first. We also measured levels of subjective anxiety and fear of scrutiny . Results: Subjects randomized to receive DCS prior to their first speech were more likely to show between‐session habituation than those who received placebo. We also found greater reduction of performance‐related fear overall in the DCS group . Conclusion: Our clinical assay was able to detect exposure facilitation effects rapidly and in a highly standardized way, and is estimated to take a fraction of the time and costs of a clinical trial. Given the increasing interest in using medications to enhance learning‐based psychotherapy, this high‐throughput clinical assay approach may be a favorable method for testing novel mechanisms of action, and clarifying optimal parameters, for therapy facilitation .